2018
DOI: 10.1128/aem.02068-18
|View full text |Cite
|
Sign up to set email alerts
|

cis -Acting Determinant Limiting Expression of Sphingomyelinase Gene sph2 in Leptospira interrogans, Identified with a gfp Reporter Plasmid

Abstract: Many strains of the spirochete Leptospira interrogans serovar Pomona express the osmotically inducible sphingomyelinase gene sph2 at much higher levels than strains from other serovars. We developed a new green fluorescent protein (GFP) reporter plasmid to examine sph2 gene expression determinants. The vector enables the fusion of the test promoter to the ribosome-binding site and coding region of gfp. We fused the sph2 promoters from the L. interrogans serovar Lai strain 56601 and from the L. interrogans sero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The mutation in the coding sequence is silent. The resulting allelic constructs containing of the first 150 bp of the sigX gene were translationally fused to GFP ( 23 ), cloned into the pathogenic Leptospira vector pRAT724, and conjugated into wild-type and lomA L. interrogans . The resulting fluorescence was measured to compare background expression of the sigX gene with or without methyl groups (Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation in the coding sequence is silent. The resulting allelic constructs containing of the first 150 bp of the sigX gene were translationally fused to GFP ( 23 ), cloned into the pathogenic Leptospira vector pRAT724, and conjugated into wild-type and lomA L. interrogans . The resulting fluorescence was measured to compare background expression of the sigX gene with or without methyl groups (Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…All plasmid constructs used in this study are based on the leptospiral replicative vector pMaOri ( 22 ) and pRAT724 ( 23 ). A list of all strains created and used in the course of these studies can be found in Supplementary Table S4 , and the primers used in Supplementary Table S5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was of great interest to compare the activity of the potential clpB Li promoter (clpB Li P1) under basal and increased levels of σ E . To our knowledge, there has been only one report to date, describing the construction and utility of the gfp reporter plasmid for assessing promoter activity in L. interrogans [22]. Therefore, due to the still existing limitations of genetic tools that could be easily utilized for examining gene expression in L. interrogans, experiments were performed in E. coli cells.…”
Section: Presence Of a Promoter Dependent On σ E Upstream Of The Clpbmentioning
confidence: 99%
“…Such limitations have hampered efforts to identify proteins involved in cell shape, spatial localization of proteins, and transport across the periplasmic space while accommodating flagellar rotation. To address some of the molecular mechanisms underpinning these and other cellular processes, fluorescent proteins and dyes have proven to be valuable tools, permitting detection of spirochete-host interactions (Moriarty et al, 2008; Norman et al, 2008; Dunham-Ems et al, 2009; Bockenstedt et al, 2012; Carrasco et al, 2015; Teixeira et al, 2016; Krishnavajhala et al, 2017), localization or transport of proteins within the bacterial cell (Schulze and Zuckert, 2006; Schulze et al, 2010; Xu et al, 2011; Zhang et al, 2015), or as reporter systems for gene expression (Carroll et al, 2003; Bykowski et al, 2006; Clifton et al, 2006; Eggers et al, 2006; Miller et al, 2006; Gautam et al, 2008, 2009; Whetstine et al, 2009; Aviat et al, 2010; Cerqueira et al, 2011; Grove et al, 2017; Matsunaga and Haake, 2018; Takacs et al, 2018). However, the use of fluorescent protein fusions, most commonly with green or red fluorescent protein (GFP or RFP, respectively), has limitations: the bulkiness of these proteins, typically 25–30 kDa, can lead to atypical protein localization and irregular cellular trafficking (Senf et al, 2008), and some FP alleles have specific pH or oxygen requirements that are not always compatible with the targeted location or underlying biological question.…”
Section: Introductionmentioning
confidence: 99%